Quality of life after robotic‐assisted and laparoscopic radical prostatectomy: Results of a multicenter randomized controlled trial (LAP‐01). Issue 8 (7th March 2022) - Holze, Sigrun; Lemaire, Emilie; Mende, Meinhard; Neuhaus, Petra; Arthanareeswaran, Vinodh‐Kumar‐Adithyaa; Truss, Michael C.; Minh Do, Hoang; Dietel, Anja; Teber, Dogu; Stützel, Karin D.; Hohenfellner, Markus; Rabenalt, Robert; et al.
Abstract: Background: To explore cross‐sectional and longitudinal differences in general health‐related and prostate cancer‐specific quality of life (QoL) after robotic‐assisted (RARP) and laparoscopic (LRP) radical prostatectomy and to analyze predictive variables for QoL outcomes. Methods: In this multicenter, randomized controlled trial, prostate cancer patients were randomly assigned 3:1 to undergo either RARP or LRP. Patient‐reported outcomes were prospectively collected before and 1, 3, 6, 12 months after radical prostatectomy and included QoL as a secondary outcome. Validated questionnaires were used to assess general health‐related (EORTC QLQ‐C30) and prostate cancer‐specific (QLQ‐PR25) QoL. Cross‐sectional and longitudinal contrasts were analyzed through linear mixed models. Predictive variables for QoL outcomes were identified by general linear modeling. Results: Of 782 randomized patients, QoL was evaluable in 681 patients. In terms of general QoL, the cross‐sectional analysis showed only small differences between study arms, whereas longitudinal comparison indicated an advantage of RARP on recovery: RARP patients reported an earlier return to baseline in global health status (3 vs. 6 months) and social functioning (6 vs. 12 months). In role functioning, only the RARP arm regained baseline scores. Regarding prostate‐specific QoL, LRP patients experienced more urinary symptoms and reported 3.2 points (95% confidence interval 0.4–6, p = 0.024) higher mean scores at 1‐month follow‐up and in mean 2.9 points (0.1–5, p = 0.042) higher urinary symptoms scores at 3‐month follow‐up than RARP patients. There were no other significant differences between treatment groups. Urinary symptoms, sexual activity, and sexual function remained significantly worse compared with baseline at all time points in both arms. Conclusions: Compared with LRP, the robotic approach led to an earlier return to baseline in several domains of general health‐related QoL and better short‐term recovery of urinary symptoms. Predictive variables such as the scale‐specific baseline status and bilateral nerve‐sparing were confirmed.